Identification of the optimal combination dosing schedule of neoadjuvant ipilimumab plus nivolumab in macroscopic stage III melanoma (OpACIN-neo): a multicentre, phase 2, randomised, controlled trial. Issue 7 (July 2019) - Rozeman, Elisa A; Menzies, Alexander M; van Akkooi, Alexander C J; Adhikari, Chandra; Bierman, Carolien; van de Wiel, Bart A; Scolyer, Richard A; Krijgsman, Oscar; Sikorska, Karolina; Eriksson, Hanna; Broeks, Annegien; van Thienen, Johannes V; et al.
Summary: Background: The outcome of patients with macroscopic stage III melanoma is poor. Neoadjuvant treatment with ipilimumab plus nivolumab at the standard dosing schedule induced pathological responses in a high proportion of patients in two small independent early-phase trials, and no patients with a pathological response have relapsed after a median follow up of 32 months. However, toxicity of the standard ipilimumab plus nivolumab dosing schedule was high, preventing its broader clinical use. The aim of the OpACIN-neo trial was to identify a dosing schedule of ipilimumab plus nivolumab that is less toxic but equally effective. Methods: OpACIN-neo is a multicentre, open-label, phase 2, randomised, controlled trial. Eligible patients were aged at least 18 years, had a WHO performance status of 0–1, had resectable stage III melanoma involving lymph nodes only, and measurable disease according to the Response Evaluation Criteria in Solid Tumors version 1.1. Patients were enrolled from three medical centres in Australia, Sweden, and the Netherlands, and were randomly assigned (1:1:1), stratified by site, to one of three neoadjuvant dosing schedules: group A, two cycles of ipilimumab 3 mg/kg plus nivolumab 1 mg/kg once every 3 weeks intravenously; group B, two cycles of ipilimumab 1 mg/kg plus nivolumab 3 mg/kg once every 3 weeks intravenously; or group C, two cycles of ipilimumab 3 mg/kg once every 3 weeks directly followed by two cycles of nivolumab 3 mg/kg once every 2 weeks intravenously. The investigators, site staff, and patients were aware of the treatment assignment during the study participation. Pathologists were masked to treatment allocation and all other data. The primary endpoints were the proportion of patients with grade 3–4 immune-related toxicity within the first 12 weeks and the proportion of patients achieving a radiological objective response and pathological response at 6 weeks. Analyses were done in all patients who received at least one dose of study drug. This trial is registered withClinicalTrials.gov, numberNCT02977052, and is ongoing with an additional extension cohort and to complete survival analysis. Findings: Between Nov 24, 2016 and June 28, 2018, 105 patients were screened for eligibility, of whom 89 (85%) eligible patients were enrolled and randomly assigned to one of the three groups. Three patients were excluded after randomisation because they were found to be ineligible, and 86 received at least one dose of study drug; 30 patients in group A, 30 in group B, and 26 in group C (accrual to this group was closed early upon advice of the Data Safety Monitoring Board on June 4, 2018 because of severe adverse events). Within the first 12 weeks, grade 3–4 immune-related adverse events were observed in 12 (40%) of 30 patients in group A, six (20%) of 30 in group B, and 13 (50%) of 26 in group C. The difference in grade 3–4 toxicity between group B and A was −20% (95% CI −46 to 6; p=0·158) and between group C and group A was 10% (−20 to 40; p=0·591). The most common grade 3–4 adverse events were elevated liver enzymes in group A (six [20%)]) and colitis in group C (five [19%]); in group B, none of the grade 3–4 adverse events were seen in more than one patient. One patient (in group A) died 9·5 months after the start of treatment due to the consequences of late-onset immune-related encephalitis, which was possibly treatment-related. 19 (63% [95% CI 44–80]) of 30 patients in group A, 17 (57% [37–75]) of 30 in group B, and nine (35% [17–56]) of 26 in group C achieved a radiological objective response, while pathological responses occurred in 24 (80% [61–92]) patients in group A, 23 (77% [58–90]) in group B, and 17 (65% [44–83]) in group C. Interpretation: OpACIN-neo identified a tolerable neoadjuvant dosing schedule (group B: two cycles of ipilimumab 1 mg/kg plus nivolumab 3 mg/kg) that induces a pathological response in a high proportion of patients and might be suitable for broader clinical use. When more mature data confirm these early observations, this schedule should be tested in randomised phase 3 studies versus adjuvant therapies, which are the current standard-of-care systemic therapy for patients with stage III melanoma. Funding: Bristol-Myers Squibb.